celebration in the city - Grigoryeva, Elena (project baikal, 2020)
A Moveable Feast, this is the definition Hemingway gave to Paris, a big city where he spent a happy period of his life. A celebration city, a city and a celebration, celebration spaces have become the subject of the issue. And a winter city – for those cities which have got winter anyway. In Irkutsk, this topic seems to be seriously considered (p.75). In Moscow, the already traditional Journey to Christmas has lasted for the three winter months, although without natural attributes such as snow, frost and other unnecessary stuff. Meanwhile, climate change made the International Union of Architects join its efforts with the UNO and publish the Declaration (p. 5). Anyway, the luxury of the decorated center made our capital the leader among European brothers and sisters. As for the competition among cities, do non-capitals with their modest budgets have any chance to hit the podium? “They do”, says the FORBES LIFE and publishes the list of top 10 most promising cities in Russia, which includes Irkutsk. Among other things, it is due to the Winter University (its XXIst session will be featured in the next issue) and a successful Quarter 130 (see the details that have not been published before on pp. 62-69). Italian cities of Siena, Berga, Assisi and Venice can be truly called celebration cities. Cities give birth to celebrations, but a celebration can also inspire the city to start a new life. The heroes of this issue are Perm, Novosibirsk, Norilsk, Irkutsk, Ulan Bator, Dresden and Kyakhta. The city declared the World Capital of Architecture for 2020, Rio de Janeiro (pp. 6-7) will host us for the UIA Congress in July.